SYSTEMATIC LITERATURE RIVIEW: PENGARUH SELF-COMPASSION TERHADAP KESEHATAN PSIKOLOGIS REMAJA - Rizky Amaliah Putri Almajid; Iriani Indri Hapsari; Zarina Akbar (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Adolescence is a developmental stage characterized by rapid biological, emotional, and social changes, making individuals particularly vulnerable to psychological health problems. One protective factor that has received considerable attention in positive psychology is self-compassion; however, findings regarding its influence on various dimensions of adolescents' psychological health remain scattered across individual studies, highlighting the need for a comprehensive synthesis. This study aimed to examine the influence of self-compassion on emotion regulation, resilience, self-esteem, and subjective well-being among adolescents using a Systematic Literature Review (SLR) approach. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including the stages of identification, screening, eligibility assessment, and inclusion of relevant studies. Literature was retrieved from Google Scholar using Publish or Perish with the keywords "self-compassion" and "the influence of self-compassion" for publications between 2022 and 2024. Of the 205 articles initially identified, six met the inclusion criteria and were systematically analyzed. The findings consistently demonstrated that self-compassion positively influences emotion regulation, resilience, self-esteem, and subjective well-being among adolescents. This synthesis provides a comprehensive understanding of the consistent contribution of self-compassion to adolescents' psychological health and offers an empirical foundation for developing evidence-based educational programs, guidance and counseling services, and psychological interventions aimed at promoting adolescent mental well-being. ABSTRAK Masa remaja merupakan periode perkembangan yang rentan terhadap berbagai perubahan biologis, emosional, dan sosial sehingga berpotensi meningkatkan risiko munculnya permasalahan kesehatan psikologis. Salah satu faktor protektif yang banyak dikaji dalam psikologi positif adalah self-compassion, namun hasil penelitian mengenai pengaruhnya terhadap berbagai aspek kesehatan psikologis remaja masih tersebar pada berbagai studi sehingga memerlukan sintesis yang komprehensif. Penelitian ini bertujuan untuk menganalisis pengaruh self-compassion terhadap regulasi emosi, resiliensi, self-esteem, dan subjective well-being pada remaja melalui pendekatan Systematic Literature Review (SLR). Penelitian dilaksanakan dengan mengacu pada pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) yang meliputi tahapan identifikasi, penyaringan, uji kelayakan, dan inklusi artikel. Penelusuran literatur dilakukan melalui Google Scholar dengan bantuan Publish or Perish menggunakan kata kunci “self-compassion” dan “pengaruh self-compassion” pada rentang publikasi 2022–2024. Dari 205 artikel yang teridentifikasi, enam artikel memenuhi kriteria inklusi dan dianalisis secara sistematis. Hasil kajian menunjukkan bahwa self-compassion secara konsisten berpengaruh positif terhadap regulasi emosi, resiliensi, self-esteem, dan subjective well-being pada remaja. Sintesis temuan ini menegaskan bahwa self-compassion merupakan faktor protektif yang berkontribusi dalam memperkuat kesehatan psikologis remaja sekaligus memberikan dasar ilmiah bagi pengembangan program pendidikan, layanan bimbingan dan konseling, serta intervensi psikologis berbasis bukti untuk meningkatkan kesejahteraan mental remaja.